Assessment of Structural Variations in Fornix of MCI and AD Using MR Images and Geometrical Features - Ali A.; Ronickom J.F.A.; Swaminathan R. (My University, 2025)
Purpose: Mild cognitive impairment (MCI) and Alzheimer’s disease (AD) are known to cause geometrical changes in the integrity of the fornix, which plays a crucial role in memory formation and retrieval. The objective of this study is to analyse structural variations in the fornix region using structural magnetic resonance (sMR) images and geometrical features. Methods: Initially, the fornix region of the brain is segmented from the sMR images of normal cognitive (NC), MCI and AD using the FreeSurfer software package. Further, geometrical features such as volume, equivalent diameter, extent, major axis length, and solidity are extracted to investigate the changes in the structure of the fornix in MCI and AD conditions. Results: The segmentation results show that FreeSurfer software is able to delineate the irregular boundaries of the fornix region accurately. The extent, major axis length, and solidity features are found to be statistically significant (p < 0.001) in discriminating NC, MCI and AD. It indicates that the considered features can capture the geometrical variation in the fornix structure. Conclusion: The reported approach can facilitate the early diagnosis of the disease, as the distinction of AD in the preclinical stage is complex and clinically significant. © Taiwanese Society of Biomedical Engineering 2024.